2018
DOI: 10.1097/bpb.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the lateral and posterior approaches in the treatment of pediatric supracondylar humeral fractures

Abstract: This study explored the radiological, functional, and cosmetic results of treatment of supracondylar humeral fractures with open reduction and percutaneous pinning, comparing posterior triceps V-splitting (group I, n=22) and lateral (group II, n=25) approaches. The time to union, the functional and cosmetic results, and the flexor and extensor muscle strengths were measured and compared with the contralateral extremities. There were no statistical differences between the groups. The V-splitting posterior appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…6 A retrospective review study done among children with supracondylar humerus fracture by Dhoju et al showed a mean age of 8.91 years with a range of 2-14 years. 7 A single center study done by Auso-Perez et al showed that the presentation risk at nighttime was higher during the summer months. 8 Our study showed early morning hours (3 AM-6 AM) with a higher load of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 A retrospective review study done among children with supracondylar humerus fracture by Dhoju et al showed a mean age of 8.91 years with a range of 2-14 years. 7 A single center study done by Auso-Perez et al showed that the presentation risk at nighttime was higher during the summer months. 8 Our study showed early morning hours (3 AM-6 AM) with a higher load of cases.…”
Section: Discussionmentioning
confidence: 99%
“…7 A single center study done by Auso-Perez et al showed that the presentation risk at nighttime was higher during the summer months. 8 Our study showed early morning hours (3 AM-6 AM) with a higher load of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methicillin-resistant Staphylococcus aureus (MRSA), once confined mainly to healthcare-associated infections, has been increasingly reported from community. 1 The hospital-associated MRSA (HA-MRSA) is generally associated with patients with predisposing factors such as prolonged hospitalization, use of indwelling catheters, or prior surgical procedures. In contrast, community-associated MRSA (CA-MRSA) is associated with healthy and younger people without such predisposing factors.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, community-associated MRSA (CA-MRSA) is associated with healthy and younger people without such predisposing factors. 2 It has been identified that nasal colonization of S. aureus plays a key role in its pathogenesis. 3 MRSA isolates exhibit multidrug resistance; moreover, increasing reports of MRSA isolates with decreased susceptibility to glycopeptides (glycopeptide intermediately susceptible S. aureus, GISA) is a cause for great public concern.…”
Section: Introductionmentioning
confidence: 99%